Elements of Paleogene Geology of Indonesia – Part 1. History of Discovery and Biostratigraphy - J.T. (Han) van Gorsel (Ikatan Ahli Geologi Indonesia, 2026)
This introductory paper provides a comprehensive overview of the Paleogene sediments and fossils of Indonesia, synthesizing over 170 years of geological research to guide future stratigraphic studies. While less extensively studied than Neogene sequences due to fewer outcrops, fewer well penetrations, and lower economic hydrocarbon discoveries, Paleogene successions (66–23 Ma) offer critical insights into distinct paleoclimatic and paleotectonic regimes. The paper focuses on the history of discovery, biostratigraphic concepts, and the distinct characteristics of three regional paleotectonic domains (Eurasian, Gondwanan, and SW Pacific) that amalgamated into a complex mosaic of sedimentary basins. This paper discusses first discoveries of Paleogene deposits in Indonesia, Paleogene biostratigraphy and the terrestrial world of Paleogene sequence.